2017
DOI: 10.1111/risa.12773
|View full text |Cite
|
Sign up to set email alerts
|

Who is a Distracted Driver? Associations between Mobile Phone Use while Driving, Domain‐Specific Risk Taking, and Personality

Abstract: Mobile phone use while driving (MPUWD) is an increasingly common form of distracted driving. Given its widespread prevalence, it is important for researchers to identify factors that may predict who is more likely to engage in this risky behavior. The current study investigates associations between MPUWD risk behaviors, domain-specific risk perceptions, and broad personality dimensions. An Italian community sample (n = 804) completed a survey regarding MPUWD risk perceptions and engagement in MPUWD, in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 76 publications
3
32
0
Order By: Relevance
“…Drivers with higher disinhibition scores are associated with more likelihood of distracted driving in any of the scenarios tested. The results confirm some previous studies that linked disinhibition (Sanbonmatsu, Strayer, Medeiros-Ward, & Watson, 2013;Sween et al, 2017) and personality (Sween et al, 2017) with multitasking activity and mobile phone use while driving. The disinhibition component of sensation seeking is associated with ''seeking release'' or ''disinhibited social behavior.''…”
Section: Driver Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…Drivers with higher disinhibition scores are associated with more likelihood of distracted driving in any of the scenarios tested. The results confirm some previous studies that linked disinhibition (Sanbonmatsu, Strayer, Medeiros-Ward, & Watson, 2013;Sween et al, 2017) and personality (Sween et al, 2017) with multitasking activity and mobile phone use while driving. The disinhibition component of sensation seeking is associated with ''seeking release'' or ''disinhibited social behavior.''…”
Section: Driver Characteristicssupporting
confidence: 91%
“…In addition, personality factors have been reported to be of great importance in the study of mobile phone use while driving. A recent study by Sween, Ceschi, Tommasi, Sartori, and Weller (2017) suggested that drivers' personality (sensation seeking, honesty/humility, and conscientiousness) is related to risky driving behaviors and risk perception. Therefore, without a proper consideration of these unobserved variables, it may not be realistic to assume that the effects of the available explanatory variables can be equally applied across all individuals.…”
Section: Analytical Approachmentioning
confidence: 99%
“…By introducing smartphone addiction as the potential mediating variable, Kita and Luria (2018) displayed openness to experience decreased while extraversion and neuroticism increased the likelihood of smartphone use while driving, but the moderation effect of smartphone addiction only worked on the relationship between neuroticism and smartphone use while driving. Sween, Ceschi, Tommasi, Sartori, and Weller (2017) recorded risk perceptions acted as a mediating role on the relationships between four HEXACO dimensions (honesty/humility, conscientiousness, openness and emotionality) and the self-reported frequency of mobile phone use while driving. These studies confirm that certain personality traits significantly correlate to MPUWD behaviors, and that there may be some variables moderate the effects of personality traits on MPUWD behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 16-item MPUWD risk perception scale was previously developed to assess the associated risk attitudes to MPUWD (Weller, Shackleford, Dieckmann, & Slovic, 2013), which had been modified to investigate the correlation between MPUWD and its corresponding risk perceptions (Mirman, Durbin, Lee, & Seifert, 2017;Sween et al, 2017). Respondents were asked to complete a modified version of this scale to indicate their perceived risks by performing mobile phone tasks when driving for food delivery (e.g., "Browsing WeChat's Moments while driving takes a person's eyes off the road for too long.…”
Section: Mpuwd Risk Perceptionmentioning
confidence: 99%
“…In a more recent development, there has been an increasing interest in the contribution of intangible soft factors to risk, an aspect often neglected in the past due to difficulty in quantification. Using a myriad of different approaches, soft factors ranging from organizational safety culture (Guldenmund, 2010) to personal beliefs (Nakayachi, Johnson, & Koketsu, 2018) and personalities (Sween, Ceschi, Tommasi, Sartori, & Weller, 2017) are now being considered in many risk studies.…”
Section: Shortfallsmentioning
confidence: 99%